2021
DOI: 10.1021/acs.chemrev.0c00798
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Tissue Adhesives

Abstract: Polymeric tissue adhesives provide versatile materials for wound management and are widely used in a variety of medical settings ranging from minor to life-threatening tissue injuries. Compared to the traditional methods of wound closure (i.e., suturing and stapling), they are relatively easy to use, enable rapid application, and introduce minimal tissue damage. Furthermore, they can act as hemostats to control bleeding and provide a tissue-healing environment at the wound site. Despite their numerous current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
448
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(449 citation statements)
references
References 527 publications
1
448
0
Order By: Relevance
“…The hydrogel biodegradability could be potentially controlled depending on the requirements by modifying the polymer chains (Alg and PAM) with enzyme‐reacting functional groups or with non‐reactive long side chains (branches). [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogel biodegradability could be potentially controlled depending on the requirements by modifying the polymer chains (Alg and PAM) with enzyme‐reacting functional groups or with non‐reactive long side chains (branches). [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Such core-shell structures have gained increasing interest as nature-inspired phase-flexible constructs which can be exploited as biocompatible 3D hollow scaffolds to simulate organoids or mini tissues with cavity configuration, multi-release models, hierarchical bioreactors, tailor-made cells, or selective membranes to separate biomolecules statically and dynamically together with other progressive approaches. [11,[23][24][25][26] Developing core-shell microgels from proteins and their mechanical characterization is a key enabling technology in biomaterial mechanics research and regenerative medicine. Previous studies have showed the generation of core-shell non-protein microgels using two-step microfluidic techniques, 3D nested microcapillaries, or non-microfluidic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional tissue adhesives and sealants could be used in cases of blood vessel anastomosis, lung leakage preventions, and incision closure. Examples of tissue adhesives and sealants are cyanoacrylates, albumin, glutaraldehyde, polyethylene glycol (PEG) polymers, and fibrin sealant ( Ge and Chen, 2020 ; Nam and Mooney, 2021 ). Tissue adhesives and sealants are also used as glue for the application of non-adhesive scaffold devices, aiding to fix the scaffold on the surface of organs and tissues ( Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%